Effects of Dual Symbiotic Interactions Performed by the Exotic Tree Golden Wreath Wattle (Acacia cyanophylla Lindl.) on Soil Fertility in a Costal Sand Dune Ecosystem - Dounas, Hanane; Bourhia, Mohammed; Outamamat, Elmostapha; Bouskout, Mohammed; Nafidi, Hiba-Allah; El-Sheikh, Mohamed A.; Al-Abbadi, Ghanim A.; Ouahmane, Lahcen (Frontiers in Environmental Science, 2022)
The present study aims to evaluate the effects of the exotic shrub Acacia cyanophylla Lindl. on soil fertility by studying (i) its ability to modify the soil physicochemical composition, (ii) its contribution to the soil mycorrhizal potential and its impact on the richness and diversity of the arbuscular mycorrhizal fungi (AMF) community in the rhizospheric soil (RS), and finally (iii) its atmospheric nitrogen fixation potential. The physicochemical analysis of the RS has shown that soil invasion by A. cyanophylla has a beneficial effect on its fertility; this advantage is demonstrated by the increase of the organic matter and the nutrient contents (N, P, K, Na, Ca) in the RS. Furthermore, the roots of this shrub exhibited broad AMF colonization, which confirms its high mycotrophic aspect. Four differentiated morphotypes of mycorrhizal spores were isolated from the RS of A. cyanophylla by use of the wet sieving method. In addition, the most probable number method showed that A. cyanophylla was capable of dramatically increasing the mycorrhizal potential of the soil. Indeed, more than 1213 infectious propagules per one hundred grams of soil were detected in the RS of A. cyanophylla. Moreover, A. cyanophylla roots showed a significant presence of nodules indicating an active atmospheric nitrogen fixation. Counting revealed the presence of at least 130 nodules in the root fragments contained in 1 kg of soil. In conclusion, the biological invasion of sand dunes by the exotic shrub A. cyanophylla exhibited beneficial effects on the soil’s chemical composition and functioning, the activity of rhizobacteria in fixing atmospheric nitrogen, and phosphate bioavailability under the action of the native AMF community.